2017
DOI: 10.1177/0021934717729504
|View full text |Cite
|
Sign up to set email alerts
|

Pop Culture Without Culture: Examining the Public Backlash to Beyoncé’s Super Bowl 50 Performance

Abstract: On February 7, 2016, Beyoncé took the stage of Super Bowl 50 as a featured artist during the halftime show. Immediately after, her performance was classified as an anti-American act of terrorism. The public took to social media, not in the usual fan craze, but to condemn and damn Beyoncé for her celebration of Black culture. This condemning is a reflection of the marginalized treatment of Black popular artists which prohibits them from speaking out on Black issues. Consequently, Black popular artists are force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Since 2016, the connection between football and American nationalism has changed especially with the rising of evidence of police brutality and racial discrimination against African Americans, a demographic that is overrepresented in the sport (Woods and Butler 2021 ). Beyoncé’s performance in the 2016 halftime show was deemed “anti-police and anti-American” (Gammage 2017 ) by policy unions and the public. Later that year, populist Presidential Candidate Donald Trump criticized Colin Kaepernick and other NFL players for protesting during the national anthem and disrespecting the flag (Cooper 2019 ).…”
Section: Football and Brand Americamentioning
confidence: 99%
“…Since 2016, the connection between football and American nationalism has changed especially with the rising of evidence of police brutality and racial discrimination against African Americans, a demographic that is overrepresented in the sport (Woods and Butler 2021 ). Beyoncé’s performance in the 2016 halftime show was deemed “anti-police and anti-American” (Gammage 2017 ) by policy unions and the public. Later that year, populist Presidential Candidate Donald Trump criticized Colin Kaepernick and other NFL players for protesting during the national anthem and disrespecting the flag (Cooper 2019 ).…”
Section: Football and Brand Americamentioning
confidence: 99%
“…However, I found that other disciplines have yet to explore this research topic, from their respective contexts, as well. Instead, the most closely related research topics in this area (Gammage, 2017;McNally, 2016;Emerson, 2002), mainly focused on exemplary cases of "misogynoir 45 " (Bailey, 2014;Bailey, 2016;Bailey & Trudy, 2018) and other forms of bigotry encountered by Black women in music, in the public sphere, which were framed as occurring under the "White gaze" or the "male gaze" 46 . Since the primary focus of much of the available scholarship, seemed to maintain a particularly heavy concentration on Black women in music, in visual popular culture, these studies could not inform the broader scope of my research, although these could help inform other aspects of insights, that may be found in the research, at a later stage.…”
Section: Chapter 7: Conclusion and Recommendationsmentioning
confidence: 99%